Steuerung lokalisierter Projektnetzwerke am Beispiel der Produktion von TV- Sendungen in den Medienclustern München und Köln - Moßig, Ivo (ERDKUNDE, 2004)
The production of television programmes in Germany is confined to a few specific locations. This study examines the organisational structures for producing TV programmes within interlinked production networks. Data about the two main centres, Munich and Cologne, was collected and analysed in detail. These networks feature a high degree of inter-company division of labour and flexible specialisation of the individual enterprises. A further feature is the project-specific composition of the value chain. The main aim of the study was to explore the mechanisms directing and controlling the local networks. The balance of power between the individual economic players is unequal and decision-making competencies are unevenly distributed. The study argues that this imbalance of power constitutes a functional element of the local networks by significantly expediting the decision-making process. This is demonstrated using an exemplary case study. The imbalance of power already becomes evident when looking at the process of selecting individual companies for a TV production. This selection process occurs within a centralised mechanism and is dominated by a few individuals occupying certain key positions. Selection criteria are ruled by socio-institutional relations such as personal contacts, previous successful cooperation, recommendations and reputation.